Brides of Laurent: A Daughter's Courage - Book 3 - Beller, Misty M. (Minneapolis, Minnesota : Bethany House, a division of Baker Publishing Group, 2022)
"Charlotte Durand sets out on an expedition in search of a skilled artisan who can repair a treasured chalice-but her hike becomes much more daunting when a treacherous snowstorm sets in. When Damien Levette finds Charlotte stranded, they must work together to survive the peril of the mountains against all odds"--
Keywords: Quests (Expeditions) -- Fiction; Man-woman relationships -- Fiction; Survival -- Fiction; Christian fiction; Romance fiction; Novels